An Overview of the Burial Complexes and Human Skeletal Remains from the Markula Hillfort (Ochamchira District, Republic of Abkhazia) - Albert G. Yurkov (Археология евразийских степей)
The article provides a summary description of burial complexes containing paleoanthropological material discovered during the study of the Markula hillfort—a site of the ancient Abkhaz population, located in the southeastern part of the Republic of Abkhazia, 10 km from the coast, near the ancient Greek polis of Guenos, an antique colony in Colchis. Research at the site has been ongoing since 2014, and during this period, layers dating from the XVIII century (a Muslim cemetery on the site of a former temple) to the IV century BC (a Hellenistic-era crypt) have been excavated. In addition to direct archaeological findings, paleoanthropological material has also been accumulated over this period—partially studied by T.Y. Shvedchikova (2014–2017 samples) and as-yet unstudied (2018–2024 samples). It is worth noting a factor reflecting the specificity of ancient Abkhaz sites, which finds confirmation in modern ethnography. This factor lies in the fact that burial sites were located near dwellings and other domestic structures. This article presents a brief overview of the paleoanthropological finds from different areas of the settlement, with indications of their dating, skeletal completeness, and preservation state. Furthermore, the prospects for further research are outlined.